MOONLIGHT study: the design of a comparative study of the effectiveness of belimumab in patients with a history of lupus nephritis from the post-Marketed effectiveness of belimumab cOhOrt and JapaN Lupus NatIonwide reGistry (LUNA) coHorT. Issue 1 (1st September 2022) - Sada, Kenei; Kurita, Noriaki; Noma, Hisashi; Matsuki, Taizo; Quasny, Holly; Levy, Roger A; Jones-Leone, Angela R; Gairy, Kerry; Yajima, Nobuyuki
Abstract : Introduction: Lupus nephritis (LN) is more prevalent in patients with SLE of Asian ethnicity than in Caucasian patients. Belimumab became available in Japan in 2017 to treat patients with SLE, including those with LN. In the BLISS-LN trial (NCT01639339 ), belimumab showed a favourable effect on renal outcomes when combined with standard therapy (ST) starting at the induction treatment phase for active LN, but real-world effectiveness of belimumab in LN has not been extensively studied. Here we describe the protocol for the MOONLIGHT (post-Marketed effectiveness of belimumab cOhOrt and JapaN Lupus NatIonwide ReGistry (LUNA) coHorT) study, which will use data from a Japan postmarketing surveillance study and the Lupus Registry of Nationwide Institutions (LUNA) to evaluate the real-world effectiveness of belimumab plus ST versus ST alone in patients with a history of active LN who are not in the induction phase. Methods and analysis: This multicentre, retrospective, observational study (GSK Study 214710) will enrol adults with SLE and a history of active LN, holding ≥3 years of complete follow-up data from the initiation of belimumab (no continuous treatment required). Data for patients with belimumab plus ST treatment (postmarketing registry data, belimumab cohort) will be compared with those for patients with ST only treatment (LUNA data, comparison cohort). Patients who discontinue/initiate belimumab after the start of the follow-up may be included in the comparison/belimumab cohort, respectively. The primary endpoint will be the occurrence of renal flares, for which belimumab's effectiveness will be estimated using a marginal structural model to consider time-dependent treatment and confounding factors. Secondary endpoints will include change in corticosteroid dose, renal disease activity, extrarenal disease activity, disease severity/activity biomarkers, LN class changes, end-stage kidney disease events and hospitalisations. Ethics and dissemination: This study will be conducted according to the Declaration of Helsinki and the local ethical guidelines. Findings will be submitted to peer-reviewed journals and presented at scientific meetings.